Effects of Bu Shen Yi sui capsule on NogoA/NgR and its signaling pathways RhoA/ROCK in mice with experimental autoimmune encephalomyelitis - Ling Fang; Yongqiang Wang; Qi Zheng; Tao Yang; Peiyuan Zhao; Hui Zhao; Qiuxia Zhang; Yuanyuan Zhao; Fang Qi; Kangning Li; Zhenzhen Chen; Junling Li; et al. (BMC, 2017)
Abstract Background Axon growth inhibitory factors NogoA/Nogo receptor (NgR) and its signaling pathways RhoA/Rho kinase (ROCK) play a critical role in the repair of nerve damage in multiple sclerosis (MS). Bu Shen Yi Sui Capsule (BSYSC) is an effective Chinese formula utilized to treat MS in clinical setting and noted for its potent neuroprotective effects. In this study, we focus on the effects of BSYSC on promoting nerve repair and the underlying mechanisms in mice with experimental autoimmune encephalomyelitis (EAE), an animal model of MS. Methods The EAE mouse model was induced by injecting subcutaneously with myelin oligodendrocyte glycoprotein (MOG) 35-55 supplemented with pertussis toxin. BSYSC was orally administrated at dose of 3.0 g/kg once a day for 40 days. The levels of protein gene product (PGP) 9.5, p-Tau, growth associated protein (GAP) -43, KI67 and Nestin in the brain or spinal cord on 20 and 40 day post-induction (dpi) were detected via immunofluorescence and Western blot analysis. Furthermore, NogoA/NgR and RhoA/ROCK signaling molecules were studied by qRT-PCR and Western blot analysis. Results Twenty or 40 days of treatment with BSYSC increased markedly PGP9.5 and GAP-43 levels, reduced p-Tau in the brain or spinal cord of mice with EAE. In addition, BSYSC elevated significantly the expression of KI67 and Nestin in the spinal cord 40 dpi. Further study showed that the activation of NogoA/NgR and RhoA/ROCK were suppressed by the presence of BSYSC. Conclusions BSYSC could attenuate axonal injury and promote repair of axonal damage in EAE mice in part through the down-regulation of NogoA/NgR and RhoA/ROCK signaling pathways.